The Impact of Islamic Economics and Finance Courses on Islamic Financial Literacy - Alfarisi, Mohamad Fany; Agestayani, A.; Delfiani, Silvi (Ekonomi Syariah IAIN Kudus, 2020)
The present study seeks to investigate the impact of Islamic economics courses on Islamic financial literacy of university students. Additionally, it intends to compare Islamic financial literacy of those who have taken Islamic economics and finance courses and those who have not. With respect to the approach, the current study employed a quantitative approach to explain the linkage between the two variables. The population of the present study was all currently enrolled students of public universities in Padang particularly those from the faculty of economics and business. A self-administered questionnaire had been used to collect primary data. From the total distributed questionnaire, 300 of them were completed and included in the sample. As a result the respond rate is 71.3%. The results show 145 respondents are in the category of having poor Islamic financial knowledge, while 155 respondents are in the category of moderate From 145 respondents with poor Islamic financial knowledge 79 respondents (66%) have (not) taken (any) Islamic economics and finance courses. From 155 respondents with moderate financial knowledge 114 respondents (41%) have not taken any Islamic economics and finance courses. The findings of the present study suggest that most respondents can be categorized as having moderate knowledge and attending formal Islamic economics and finance courses can positively contribute to have a greater level of Islamic financial literacy.